The role of microfibrillar‐associated protein 2 in cancer - Xu, Wanzhen; Wang, Manfeng; Bai, Yang; Chen, Yong; Ma, Xiaoshan; Yang, Zhiqing; Zhao, Liyan; Li, Yunqian (Frontiers in Oncology, 2022)
Microfibrillar-associated protein 2 (MFAP2), a component of the extracellular matrix, is important in controlling growth factor signal transduction. Recent studies have shown that MFAP2, an effective prognostic molecule for various tumors, is associated with tumor occurrence and development and may be involved in remodeling the extracellular matrix and regulating proliferation, apoptosis, invasion, tumor cell metastasis, and tumor angiogenesis. However, MFAP2’s specific mechanism in these tumor processes remains unclear. This article reviewed the possible mechanism of MFAP2 in tumorigenesis and progression and provided a reference for the clinical prognosis of patients with cancer and new therapeutic target discovery.